Penetration Testing with the Bash Shell - Makan, Keith (Packt Publishing, Limited, 2014)
An easy-to-understand, step-by-step practical guide that shows you how to use the Linux Bash terminal tools to solve information security problems. If you are a penetration tester, system administrator, or developer who would like an enriching and practical introduction to the Bash shell and Kali Linux command-line-based tools, this is the book for you.